Incidence and Characteristics of Retinopathy of Prematurity Patients With Late Gestational Age and Large Birth Weight in South China - Gao, Xiang; Liao, Yunru; Lin, Duoru; Wang, Lisha; Yu, Deying; Li, Zijing; Zhang, Yichi; Lan, Yuqing (Frontiers in Medicine, 2022)
Purpose: To investigate the incidence and characteristics of retinopathy of prematurity (ROP) premature infants with late gestational age (GA) and large birth weight (BW) and show a 7-year trend of ROP incidence in South China. Methods: This retrospective, cross-sectional study included premature infants who received ROP screening in a 7-year period (from 2010 to 2016) at the Sun Yat-Sen Memorial Hospital (SYSMH), Guangzhou, South China. Infants were screened if they had GA <37 weeks or BW <2500 grams (g). All screened infants were divided into two groups: Group 1 (with both GA ≥35 weeks and BW ≥1750 g) and Group 2 (others). The characteristics of ROP infants in Group 1 were analysed and compared with those in Group 2. Results: A total of 911 premature infants were screened, with 282 infants in Group 1 and 629 in Group 2. Both the incidences of any ROP (6.7% vs. 8.3%, p=0.50) and Type 1 ROP (1.4% vs. 1.7%, p=0.72) in Group 1 were comparable with those in Group 2. Lower proportions of respiratory distress (15.8% vs. 71.2%, p<0.001), blood transfusion (5.3% vs. 32.7%, p=0.028), and oxygen administration (31.6% vs. 86.5%, p<0.001) among ROP patients in Group 1 than those in Group 2 were revealed. Vaginal delivery (OR: 4.73 [1.83-12.26]) was identified as a factor associated with ROP among the infants in Group 1. Forty percent (6/15) of Type 1 ROP in this study would have been missed under the current screening criteria in China (GA ≤ 34 weeks and/or BW ≤ 2000 g). Trends of increased incidence of Type 1 ROP and decreased BW were exhibited in the 7-year study period. Conclusions: These findings indicate that even the premature infants with late GA and large BW also have a high risk of developing ROP, especially for those delivered by vagina. The findings may provide a significant reference for ROP screening and neonatal care in South China and other regions with similar conditions.